NLRs in plant immunity: Structural insights and molecular mechanisms - Qingshuo Gu; Shasha Liu; Zuhua He; Xiangzong Meng; Yiwen Deng (Crop Design)
Plants defend against pathogens by employing intracellular NLR (nucleotide-binding leucine-rich repeat) receptors to detect pathogen effectors and initiate immune responses. While some NLRs function independently, increasing evidence reveals that many NLRs act in single, pairs or within immune networks, involving cooperative or antagonistic interactions mediated by domains such as TIR, CC, or integrated decoy domains. Recent structural breakthroughs have shown how NLRs assemble into oligomeric resistosomes, such as ZAR1 and Sr35 forming Ca2+-permeable channels, and TNL resistosomes acting as NADases to generate signaling molecules. These molecules are sensed by EDS1–PAD4 or EDS1–SAG101 complexes, which subsequently activate helper NLRs like ADR1s and NRG1s to mediate defense signaling and cell death. Moreover, novel regulatory mechanisms and negative regulators are being uncovered. These advances offer mechanistic insights into the NLR immune network and provide valuable insight into novel R gene design and molecular breeding for crop disease resistance.